ANTIBACTERIAL ACTIVITIES OF THYMUS SERPYLLUM ESSENTIAL OIL (Biological Sciences - PJSIR, 2003)
The antibacterial activity of the essential oil of Thymus serpyllum Linn. varied against gram positive bacteria (Bacillus megaterium, B. subtilis, Lactobacillus acidophilus, Micrococcus leuteus, Staphylococcus albus, S. aureus, Vibrio cholera) and gram negative bacteria (Escherichia coli, Salmonella typhi, Shigella ferrarie). The oil showed activity even at 50mg concentration. The antibacterial activity was comparable with standard antibiotics, Amoxil, Streptomycin and Kanamycin at same concentration against some of the gram positive and gram negative bacte- ria. At higher concentrations all the bacterial strains were more sensitive to oil than the standard antibiotics. The minimum inhibitory concentration (MIC) and minimum bactericidal/bacteriostatic concentration (MBC) of oil ranged between 90-170 mg ml-1  against the susceptible  bacteria.